Primary vitreoretinal involvement and immunopositivity for BRAFV600E help distinguish metastatic from primary intraocular melanoma: a detailed histopathologic study of metastatic cutaneous melanoma to the eye. Issue 7 (27th April 2022) - Neerukonda, Vamsee K; Kim, Ivana K; Stagner, Anna M
Abstract : Objective: To evaluate the clinicopathologic characteristics of metastatic cutaneous melanoma to the eye and identify potential distinguishing characteristics from the more common primary uveal melanoma; particularly, tumour location within the eye, cytomorphology and immunohistochemical/specific molecular genetic features. Methods: A retrospective observational case series using surgical enucleation and diagnostic vitrectomy cytologic specimens from seven patients with suspected intraocular melanoma, eventually diagnosed as metastatic melanoma, was conducted. Haematoxylin and eosin‐stained sections of tumour and immunohistochemical (IHC) stains for BRAFV600E and Ki‐67 were critically reviewed; BAP1 IHC was also evaluated in cases where additional tissue was available. Clinical imaging studies and medical records were reviewed. Results: The majority of patients (86%) with metastatic melanoma have primary vitreoretinal (not uveal) involvement and epithelioid, highly malignant cytomorphology (100%); many (50%) harbour BRAFV600E mutations, a finding not seen in large cohorts of primary uveal melanoma. Conclusions: Characteristics favouring or defining metastatic intraocular melanoma over primary uveal melanoma include high‐grade epithelioid cytology, predominant involvement of the vitreous cavity and/or retina, and presence of positive immunostaining for BRAFV600E. Abstract :